Development of nanocrystalline thick film gas sensors - Abadi, Mohammad Hadi Nezhad Shahrokh (2010)
In the last three decades along with growing industries and development of cities,many pollutants have entered into the environment cycle. Some resultants of these contaminations can be felt as air pollution. Now, many cities across the world have been equipped with the databases to collect and analyze the information related to air quality and to give the index of air pollution known as API. In order to record and monitor the pollution, some of those databases use advanced equipment and instrument which are very expensive and need regular overhaul and maintenance. However, some databases are equipped with simpler gas detectors, so-called solid state gas sensors. Nowadays, many types of solid state gas sensors, employed different techniques of fabrication, are released in the market. One of those techniques is known as Thick Film Technology which has proved to be very promising and low cost option to fabricate gas sensors for gas analyzers, but some problems still are associated to their efficiency such as deficient of selectivity, influence of humidity, cross sensitivity, response time, and power consumption. The main goal of this doctoral thesis is to develop a nanocrystalline metal oxide thick film gas sensor using print screen technology having fast response time and highly sensitive to air contaminants. The fabricated gas sensor consists of a heater, an electrode, and a sensitive film onto an alumina substrate, which can stand up to high firing temperature during fabrication and operation. To fabricate the sensitive paste, tin dioxide (SnO2) and tungsten trioxide (WO3) were used as the base powders. Meanwhile, platinum,silver, and yttria (Y2O3) were used as additives and dopings. Finally, types of alcohol (ethyl alcohol, isopropanol, and methanol), hydrocarbon (xylene,isobutane), ketones (acetone), mixture of inorganic gases (exhaust fumes), and wood smoke were applied to the sensors for measurement. Fabrication of the sensitive paste has brought the development of a novel vehicle binder in the organic phase of the paste. The novel binder fulfills the screen printing criteria in which can be prepared very fast, having less additional material with at least one month shelf life. Crystallite size of sensitive powder of the sensors was measured using XRD analysis, showing sizes less than 30 nm and 20 nm for metal oxide phase and metal additives, respectively. Low dependency of WO3 sensors doped with Y2O3 to humidity was observed. Sensitivity of fabricated sensors in the presence of applied gases was compared to some commercial sensors and higher sensitivity was observed. The 0.9WO30.1Y2O3 sensor (WY-90) shows to be very sensitive to organic solvents compared with sensitivity of TGS2620 (Alcohol Sensor). The 0.98SnO20.02Pt sensor (SnPt-980) shows to be more sensitive with faster response time to organic solvents and truck exhaust gas than the commercial sensors of TGS2602 (Air Quality Taguchi Sensor), TGS3870 (Methane and Carbon Monoxide), and TGS4160 (Carbon Dioxide). It shows a response time as low as 15 seconds in the presence of 500 ppm exhaust gas compared to 28 seconds response time of TGS2602. Since the sensor is equipped with a heater element, it can operate at different working temperatures and produce different sensing signal in the presence of different gases or solvents, lead to have a selective gas sensor. Also, the approach of screen printing fabrication eases the fabrication of an array of four individual gas sensors with a very thin metal oxide and catalyst layer, using pulse laser ablation deposition (PLAD) technique. The results show that the response time of the array is significantly decreased to as low as 5 seconds in the presence of 200 ppm acetone.